Sustainable and Selective Modern Methods of Noble Metal Recycling. (14th December 2022) - Zupanc, Anže; Install, Joseph; Jereb, Marjan; Repo, Timo
Abstract: Noble metals exhibit broad arrange of applications in industry and several aspects of human life which are becoming more and more prevalent in modern times. Due to their limited sources and constantly and consistently expanding demand, recycling of secondary and waste materials must accompany the traditional mineral extractions. This Minireview covers the most recent solvometallurgical developments in regeneration of Pd, Pt, Rh, Ru, Ir, Os, Ag and Au with emphasis on sustainability and selectivity. Processing—by selective oxidative dissolution, reductive precipitation, solvent extraction, co‐precipitation, membrane transfer and trapping to solid media—of eligible multi‐metal substrates for recycling from waste printed circuit boards to end‐of‐life automotive catalysts are discussed. Outlook for possible future direction for noble metal recycling is proposed with emphasis on sustainable approaches. Abstract : Recently developed solvometallurgical methods with the emphasis on green reagents, solvents and strategies are discussed in recycling noble metals Pd, Pt, Rh, Ru, Ir, Os, Ag and Au. Sustainable and separative techniques including selective dissolution, precipitation and coordination for processing of multi‐metal substrates like end of life catalysts and WEEE are highlighted.